2011
DOI: 10.1111/j.1365-2850.2010.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Disengaging from acute inpatient psychiatric care: a description of service users' experiences and views

Abstract: The growing number of people worldwide with mental health problems is increasing and making intensive demands on existing services. Recent reorganizations of healthcare provision in the UK have focused predominantly on administrative efficiency, standardization and cost-effectiveness. Although little evidence exists that reorganizations, per se, directly result in improved health nationally, nevertheless, organizational change coupled with improved care provision can have a considerable impact on the mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 46 publications
(91 reference statements)
4
63
0
1
Order By: Relevance
“…The session topics that were most highly rated as beneficial included: identifying positive coping strategies, long-term goals, support systems, positive thoughts, and a balanced daily schedule. These results reflecting clients' personal experience with occupational therapy while hospitalized highly C. E. Synovec support previous research findings in both occupational therapy and recovery model literature (Gibson et al, 2011;Nolan et al, 2011). It is beneficial to note that the consumers identified evidence-based topic areas focusing on empowerment and occupational engagement as beneficial to their recovery, demonstrating a consistent relationship between occupational therapy and recovery concepts.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The session topics that were most highly rated as beneficial included: identifying positive coping strategies, long-term goals, support systems, positive thoughts, and a balanced daily schedule. These results reflecting clients' personal experience with occupational therapy while hospitalized highly C. E. Synovec support previous research findings in both occupational therapy and recovery model literature (Gibson et al, 2011;Nolan et al, 2011). It is beneficial to note that the consumers identified evidence-based topic areas focusing on empowerment and occupational engagement as beneficial to their recovery, demonstrating a consistent relationship between occupational therapy and recovery concepts.…”
Section: Discussionsupporting
confidence: 83%
“…Social skills training is effective in decreasing symptoms in the inpatient setting as well as promoting a more successful reentry into the community (Gibson et al, 2011;Nolan et al, 2011). Social skills training has been shown Recovery Model Principles in Inpatient Psychiatric Settings to improve socialization in the community and can be a distinct role for occupational therapists within acute care settings (Gibson et al, 2011;Synovec, 2014).…”
Section: Communication Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Radcliffe and Smith (2007) found that only 6% of inpatient service-users' time was spent in therapeutic interaction with staff or activity groups, and Whittington and McLaughlin (2000) found that only 7% of nurses' time was spent in therapeutic interactions. The availability of therapeutic interaction is affected by a number of factors (Nolan, Bradley, & Brimblecombe, 2011), including the loss of skilled staff to better paid jobs in community care, a resulting reliance on bank staff (meaning a reduction in continuity of care), a lack of (psychologically-oriented) staff skills (Samarasekera, 2007), a lack of time to build the relationships necessary for personalized treatment and complex interventions (Yawar, 2008), and a lack of clarity regarding the aims of hospitalization and what constitutes appropriate treatment (Nolan et al, 2011). Our participants, including staff, agreed that hospitalization must better address service-users' needs and adequately prepare them for discharge and recovery to reduce the likelihood of relapse or long-term illness.…”
Section: Feedback Groupsmentioning
confidence: 99%